The Impact of Corporate Sustainability on Financial Reporting Quality Considering the Mediating Role of Risk - Jalilzadeh Shirvani, Seyyed Amirreza (Business, Marketing, and Finance Open, 2025)
The present study aims to examine the impact of corporate sustainability on financial reporting quality, considering the mediating role of risk. In terms of purpose, this research is applied, and in terms of methodology, it is a descriptive-correlational study. The data are panel data and were collected using information obtained from the CODAL database and Rahavard Novin software. The statistical population consists of companies listed on the Tehran Stock Exchange during the period 2020–2024. Using a screening method, a final sample of 121 companies was selected. To analyze the research model and test the hypotheses, panel data linear regression was employed using EViews software. Furthermore, the mediating effect was examined using the three-step procedure proposed by Baron and Kenny (1986). The results of the statistical analyses indicate that corporate sustainability has a positive and significant effect on financial reporting quality. The findings also reveal that risk has a negative and significant effect on financial reporting quality. Finally, based on the last stage of the Baron and Kenny technique, it was determined that risk plays a partial mediating role in the relationship between corporate sustainability and financial reporting quality.